Then Tell Me What You Think About Morality: A Freedom of Expression Perspective on the CJEU's Decision in FACK JU GÖHTE (C-240/18 P) - Tobias Endrich-Laimböck; Svenja Schenk (IIC - International Review of Intellectual Property and Competition Law, 2020)
This case note on the CJEU's decision in Fack Ju Göhte focuses on morality bars and freedom of expression in EU trade mark law. Based on the presumption that a refusal to register a trade mark for being contrary to accepted principles of morality interferes with freedom of expression, an empirical concept of morality appears incompatible with freedom of expression. However, the test for morality developed by the CJEU seems to employ such an empirical concept at least partially. In addition, the test seems to lack legal certainty. In light of freedom of expression, both represent a potential shortcoming of the decision.
Keywords: 340; Morality bars; Freedom of expression; Principles of morality; Fack Ju Göhte